2008
DOI: 10.1016/j.yjmcc.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Secoisolariciresinol diglucoside induces neovascularization-mediated cardioprotection against ischemia–reperfusion injury in hypercholesterolemic myocardium

Abstract: Background-Hypercholesterolemia (HC) induced endothelial cell dysfunction and decreased endothelial nitric oxide formation result in impaired angiogenesis & subsequent cardiovascular disorders. Therapeutic angiogenesis is known to be a novel strategy for treatment of those patients with ischemic heart disease. We have shown that secoisolariciresinol diglucoside (SDG) is angiogenic & cardioprotective against myocardial ischemia. In the present study we examined the efficacy of SDG in a hypercholesterolemic myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
(48 reference statements)
1
37
0
1
Order By: Relevance
“…These findings demonstrated that EMPs inhibited angiogenesis by inhibiting the eNOS pathway. A previous study demonstrated that eNOS expression was increased in hypercholesterolemia, which is consistent with our current findings that eNOS expression was slightly increased in LDLr Ϫ/Ϫ mice fed a Western diet for 2 wk (8,33,34). Our data showing that eNOS expression was decreased in hypercholesterolemic hearts when EMPs were present indicated that endothelial cells were quite harmful under such conditions and did not respond to exogenous angiogenic agents.…”
Section: Discussionsupporting
confidence: 92%
“…These findings demonstrated that EMPs inhibited angiogenesis by inhibiting the eNOS pathway. A previous study demonstrated that eNOS expression was increased in hypercholesterolemia, which is consistent with our current findings that eNOS expression was slightly increased in LDLr Ϫ/Ϫ mice fed a Western diet for 2 wk (8,33,34). Our data showing that eNOS expression was decreased in hypercholesterolemic hearts when EMPs were present indicated that endothelial cells were quite harmful under such conditions and did not respond to exogenous angiogenic agents.…”
Section: Discussionsupporting
confidence: 92%
“…76 SDG (20 mg/kg body wt/d for 8 weeks) reduced serum levels of TC, TG, and LDL-C by 33%, 39%, and 45%, respectively, and raised HDL-C levels by 22% in hypercholesterolemic rats. 77 …”
Section: Secoisolariciresinol Diglucosidementioning
confidence: 99%
“…Thus, hypercholesterolemic animals are more likely to experience disruption in COXIII activity; however, the specific effects shown in Figure 7 will need further analysis in order to place them in a mechanistic picture of hypercholesterolemic disruption of mitochondrial function. The lack of significant differences in the VEGF content of heart tissue from any of the groups of rabbits included in the present study is puzzling given the adverse effect on neovascularization of hypercholesterolemia observed in rats and the pivotal role played by VEGF in this process (Figure 7b) [28]. The outcome of these studies also merits further exploration in future research.…”
Section: Resultsmentioning
confidence: 82%
“…The design of these experiments was guided by an intriguing observation by other investigators that a pro-angiogenic drug called secoisolariciresinol diglucoside significantly protects against ischemia-reperfusion injury to hearts in a diet-induced hypercholesterolemic rat model by reduction of oxidative stress, accompanied by decreased infarct size of isolated hearts, increased HO-1 expression and significant increases in FS and EF [28]. This precedent underscores the importance of FS, EF and parameters for the assessment of the severity of hypercholesterolemia-associated cardiac insufficiency and therapeutic management of this and related cardiac disorders.…”
Section: Resultsmentioning
confidence: 99%